Access of energetic particles to Titan's exobase: A study of Cassini's T9 flyby - Regoli,LH; Roussos,E; Feyerabend,M; Jones,GH; Krupp,N; Coates,AJ; Simon,S; Motschmann,U; Dougherty,MK (Planetary and Space Science, 2015)
We study how the local electromagnetic disturbances introduced by Titan affect the ionization rates of the atmosphere. For this, we model the precipitation of energetic particles, specifically hydrogen and oxygen ions with energies between 1 keV and 1 MeV, into Titans exobase for the specific magnetospheric configuration of the T9 flyby. For the study, a particle tracing software package is used which consists of an integration of the single particle Lorentz force equation using a 4th order Runge–Kutta numerical method. For the electromagnetic disturbances, the output of the A.I.K.E.F. hybrid code (kinetic ions, fluid electrons) is used, allowing the possibility of analyzing the disturbances and asymmetries in the access of energetic particles originated by their large gyroradii. By combining these methods, 2D maps showing the access of each set of particles were produced. We show that the access of different particles is largely dominated by their gyroradii, with the complexity of the maps increasing with decreasing gyroradius, due to the larger effect that local disturbances introduced by the presence of the moon have in the trajectory of the particles with lower energies. We also show that for particles with gyroradii much larger than the moons radius, simpler descriptions of the electromagnetic environment can reproduce similar results to those obtained when using the full hybrid simulation description, with simple north–south fields being sufficient to reproduce the hybrid code results for O+ ions with energies larger than 10 keV but not enough to reproduce those for H+ ions at any of the energies covered in the present study. Finally, by combining the maps created with upstream plasma flow measurements by the MIMI/CHEMS instrument, we are able to estimate normalized fluxes arriving at different selected positions of the moons exobase. We then use these fluxes to calculate energy deposition and non-dissociative N2 ionization rates for precipitati